2010
DOI: 10.1029/2010gl043117
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen energization by localized perpendicular electric fields at the cusp boundary

Abstract: [1] We report Cluster observations of oxygen energization by several keV at the boundary between the high latitude cusp and lobe. A localized electric field at the cusp/lobe boundary is responsible for a significant part of the observed energization. Such electric fields can be related to the separatrix region of reconnection at the magnetopause. Ions are accelerated as they move non-adiabatically in the spatially inhomogeneous electric field. Additional heating may be provided by low frequency waves at the ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Spatial gradients of E can energize particles if ∇E > qB 2 /m [Cole, 1976;Lindstedt et al, 2010], where q is the charge of the particle and m is its mass. Spatial gradients of E can energize particles if ∇E > qB 2 /m [Cole, 1976;Lindstedt et al, 2010], where q is the charge of the particle and m is its mass.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial gradients of E can energize particles if ∇E > qB 2 /m [Cole, 1976;Lindstedt et al, 2010], where q is the charge of the particle and m is its mass. Spatial gradients of E can energize particles if ∇E > qB 2 /m [Cole, 1976;Lindstedt et al, 2010], where q is the charge of the particle and m is its mass.…”
Section: Discussionmentioning
confidence: 99%
“…An example, in which O + was accelerated at the cusp/lobe boundary by an enhanced perpendicular electric field at the boundary, was shown by Lindstedt et al . []. Takada et al .…”
Section: Discussionmentioning
confidence: 99%
“…These simu- lations are of interest for reconnection in the magnetopause with O + ions [Pritchett, 2001;Lindstedt et al, 2010]. It has been found that the O + presence does not change the reconnected flux and therefore the pace magnetic reconnection occurs.…”
Section: Discussionmentioning
confidence: 99%
“…[15] To mimic the configuration of magnetic reconnection in the magnetopause, it is useful to add an uniform out-ofplane guide field in the initial Harris sheet equilibrium [Ricci et al, 2004;Swisdak et al, 2005;Lapenta et al, 2010;Lindstedt et al, 2010;Goldman et al, 2011]. A guide field, perpendicular to the X-Y plane, B g = B 0 is imposed in the initial magnetic configuration.…”
Section: The Effect Of a Guide Fieldmentioning
confidence: 99%